A pregação em Portugal na Idade Média : alguns aspectos - Marques, José (2002)
The present research is an attempt to provide documentary evidence on the expressions and testimonies of preaching among Portuguese ecclesiastical communities in the Middle Ages – agents, possible tensions between those same agents, solutions to overcome the tensions, connections between preaching and politics ... –, and to analyse as well those testimonies first from the point of view of their structures, sources and purposes, then as proposal outline, and finally as memory sermons aiming at educating new preachers. In any case, however, those testimonies will always have to be assessed within their cultural context.